Changes in maternal conception about breastfeeding - Aline Elizabeth da Silva; Cássia Olívia Machado Campos; Maria do Carmo Fontes de Oliveira; Andréia Queiróz Ribeiro; Rosângela Minardi Mitre Cotta; Raquel Maria Amaral Araújo
Abstract Objectives: to analyze maternal conceptions about the conditions of stimulating and discouraging breastfeeding before and after the educational intervention. Methods: An intervention study type pretest/posttest was conducted for 113 women attended at a public health service. An adapted cross-cultural questionnaire was applied to identify the conceptions of pregnant women about the conditions of stimulating and discouraging breastfeeding. The effect of the intervention was verified by assessing the Decisional Balance scores before and after the intervention. Results: there was a reduction in the overall score of the discouraging conditions and an increase of the overall score of the stimulating conditions (p<0.001). In evaluating each discouraging condition, a significant reduction in the affirmative scores was observed as "breastfeeding makes the breasts saggy" (p=0.003), "I think my breasts are too small to have enough breast milk for my baby" (p=0.001). Regarding to the stimulating conditions, it showed a significant increase in the affirmative score for "breastfeeding is good for me" (p=0.006), "breastfeeding can help me lose weight" (p=0.013), "breastfeeding is easy" (p=0.004). Conclusions: the intervention resulted in changing maternal conceptions of breastfeeding and can be an interesting strategy on promoting breastfeeding in health services.